Effect of WO3 on the morphology and photodegradation of dimethyl phthalate of TiO2 nanotube array photoelectrode - Xin, Yanjun; Wang, Gang; Liu, Yongping; Zang, Zhilin; Gao, Mengchun (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
WO3 modified TiO2 nanotube array (WO3/TNAs) photoelectrodes were fabricated via electrochemical deposition on TNAs/Ti photoelectrodes. The morphology and structure of WO3/TNAs photoelectrodes were investigated by scanning electron microscopy (SEM) and X-ray diffractometer (XRD). The effects of deposition potential, deposition duration, Na2WO4 concentration, and calcination temperature on the morphology and the photocatalytic activity were investigated. The results showed that suitable amounts of WO3 promoted the photocatalytic activity of TNAs photoelectrodes for the degradation of dimethyl phthalate (DMP). The optimal conditions for the fabrication of WO3/TNAs photoelectrodes were as follows: deposition voltage 3.0 V, 10 min deposition duration, 0.01 mol/dm3 Na2WO4 concentration, 1.5 cm electrode gap, and 550 °C annealing temperature. The degradation rate of DMP reached 77% after 60 min of illumination by WO3/TNAs photoelectrode. Additionally, WO3/TNA photoelectrodes possessed superb stability for maintaining a high DMP degradation efficiency at more than 75% after 10 times of successive use with 60 min irradiation for each cycle. The enhancement of photocatalytic performance by the efficient combination of WO3 with TNAs would provide a theoretical basis for the practical application of WO3/TNA photoelectrodes in water treatment.
Environment Protection Engineering. Vol. 44, 2018, nr 3, s. 129-139
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma